(untitled) (Studia theodisca, 2022)
This article focuses on the nationalistic turn that swept across the political and cultural life of nineteenth century Germany by looking into two events that are seldom brought together: the Germanists’ Assembly in Frankfurt, in 1846, and Marx and Engels’ Manifesto of the Communist Party, published just two years later. It explores the tension between nationalism and internationalism that runs through both events and that is still vividly present in our contemporary, after all, not so «Postnational Constellation».